Analysis of the relationship between variables as one of the main tasks of economic research ("Journal "U". Economy. Management. Finance.", 2026)
The current stage of global economic development is characterized by the overlap of multiple crisis phenomena − from the effects of the COVID-19 pandemic to geopolitical conflicts and energy shocks. Under these conditions, understanding the relationships between key macroeconomic indicators is becoming more than just an academic interest; it's a practical necessity for developing anti-crisis measures. The analysis of paired relationships, such as the relationship between inflation and economic growth rates, is particularly important, as their dynamics directly impact the stability of national economies.
Keywords: linear dependencies; differentiation criterion; statistical dependencies; time series; deterministic relationships; representativeness